Lincoln's grave robbers - Sheinkin, Steve (Scholastic Focus, 2018)
Chronicles the true story of the failed attempt to steal Abraham Lincoln's body and hold it at random to secure the release of a renowned counterfeiter. Details efforts of law enforcement officials and Secret Service agents to unearth this plot and prevent it and profiles the key individuals involved.